Population dynamics of Indian scad (Decapterus russelli) in the northern and western waters of Aceh. Issue 1 (February 2021) - Damora, A; Firdiyanti, T; Rahmah, A; Aprilla, R M; Chaliluddin, M A
Abstract: Indian scad ( Decapterus russelli ) is an important commercial species that landed at the Fishing Port of Kutaradja, Banda Aceh. This research was conducted to investigate the impact of exploitation on D. russelli stock based on length-weight relationship, length distribution, length at first capture, von Bertalanffy growth parameters and function, mortality parameters, and exploitation rate. The data collection was conducted from February to March 2020 in the Fishing Port of Kutaradja, Lampulo, Banda Aceh. A total of 170 samples were measured with stratified random sampling method. Analysis of population dynamics parameters used the FAO-ICLARM Stock Assessment Tools (FiSAT) program. The results show that D. russelli has a positive allometric growth pattern, with a fork length (FL) ranging from 19.5-31.5 cm. The length of first capture was 23.1 cm. The asymptotic length ( L∞ ) of D. russelli was 31.50 cm with a growth rate ( k ) of 0.88/year and fish age at length 0 ( t 0 ) of 0.178/year. The estimated natural mortality ( M ), fishing mortality ( F ), and total mortality ( Z ) were 1.63/year, 2.22/year and 3.85/year respectively. The exploitation rate ( E ) of D. russelli was 0.58/year that indicated D. russelli in the northern and western waters of Aceh has been fully exploited.